Productive Waqf: Solutions for Strengthening the Ummah's Economy and Social Empowerment - Syahrial Arif Hutagalung; Irvan Murizal; Rizki Isnani Fadhila Saragih (Journal of Global Islamic Economic Studies, 2023)
This research focuses on optimizing the management of productive waqf as a solution for economic and social empowerment in Indonesia. With the potential for waqf reaching Rp2,000 trillion per year but the realization is still low, this study highlights the importance of transforming waqf from a consumptive to productive model to strengthen the welfare of the people. The method used is a literature review with a qualitative approach, which analyzes various sources related to the implementation of productive waqf. Data was collected from relevant journals, books, and research reports from 2018-2023. The results of the study show that the implementation of productive waqf has succeeded in increasing people's income by up to 40-60% through the creation of jobs and waqf-based business units. Technological innovations, such as the adoption of digital platforms and blockchain, play an important role in increasing transparency and accountability in waqf management. This research also underscores the importance of cross-sector collaboration and strengthening the capacity of nazhir for program sustainability. The contribution of this research lies in the development of an integrative model that combines technological, social, and economic aspects, as well as the formulation of a comprehensive monitoring system. The novelty of this study is a holistic approach that not only focuses on economic aspects, but also social empowerment and improving the quality of human resources in the productive waqf ecosystem. This research is expected to be a reference in accelerating the transformation of productive waqf for the welfare of the people in Indonesia. REFERENCES Abdullah, M. (2022). Productive Waqf Replication Model: A Comparative Study Between Regions. Journal of Waqf and Islamic Economics, 7(2), 89-104. Ahmad, S. (2022). The Role of Professional Nazhir in Optimizing Productive Waqf. Journal of Zakat and Waqf Management, 3(1), 67-82. ⁵Karim, A. (2021). Multiplier Effect of Productive Waqf on Regional Economic Growth. Economic Journal of Emerging Markets, 9(2), 156-170. Ahmad, S. (2023). Modern Waqf Management: Professionalization and Digitalization of Waqf Management. Journal of Islamic Business and Management, 8(2), 89-104. Aminah, S. (2023). Strengthening Social Capital through the Productive Waqf Program. Journal of Islamic Community Development, 7(2), 112-128. Arifin, M. (2023). Evaluation of the Impact of Waqf-Based Human Resource Development Programs. Islamic Social Sciences Quarterly, 5(1), 89-104. Aziz, M. (2023). Implementation of Blockchain Technology in Waqf Management: Opportunities and Challenges. Journal of Islamic Finance and Technology, 6(1), 67-82. Indonesian Waqf Agency. (2023). Report on the Potential and Development of Waqf in Indonesia in 2023. Jakarta: BWI Press. Fatimah, Z. (2023). Digital Literacy in Productive Waqf Management. Journal of Islamic Finance and Technology, 6(1), 23-38. Hasanah, I. (2022). Transformation of Productive Waqf: An Analysis of Economic Impact on Beneficiary Communities. Journal of Sharia Economics, 7(2), 145-160. Hassan, F. (2023). The Impact of Productive Waqf on Poverty Alleviation. Journal of Islamic Social Economics, 8(2), 123-138. Hassan, R. (2022). Digital Transformation in Waqf Management: Challenges and Opportunities. International Journal of Islamic Economics, 10(2), 156-171. Hidayat, R. (2021). Effectiveness of Training Programs in Improving the Competence of Waqf Managers. Journal of Islamic Economics and Business, 6(2), 78-93. Ismail, A. (2023). Standardization of Human Resource Development Programs in Productive Waqf Management. Islamic Management Studies, 6(1), 45-60. Ismail, I., Misrah, M., & Soemitra, A. (2022). Bibliometric Analysis of Zakat Development in Indonesia During the Covid-19 Pandemic. Jurnal Ilmiah Ekonomi Islam, 8(2), 1357-1364. Ismail, D. G., Majid, M. S. A., Marliyah, R. H., & Handayani, R. (2022). Productive zakat as a financial instrument in economic empowerment in Indonesia: A literature study. International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2(1), 83-92. Karim, A. (2022). Nazhir Capacity Building: A Study on the Effectiveness of Training and Mentoring Programs. Journal of Zakat and Waqf Management, 5(2), 112-127. Kusuma, D. (2022). Knowledge Transfer Mechanism in the Productive Waqf Program. Journal of Da'wah Management, 5(1), 67-82. Malik, S. (2022). Stakeholder Synergy in the Development of Productive Waqf. Journal of Islamic Economics and Development, 6(1), 67-82. Nugroho, B. (2023). Technological Innovation in the Management of Productive Waqf. Islamic Finance and Technology Journal, 4(2), 112-127. Rahman, A. (2020). Analysis of the Impact of the Productive Waqf Program on Improving Community Welfare. Islamic Economics Review, 8(1), 12-28. Rahman, A. (2021). Waqf-Based Economic Empowerment Theory: A Holistic Approach in the Economic Development of the People. Islamic Economics Review, 9(1), 23-38. Rahmawati, A. (2023). Transformation of Waqf Management Towards Professional Governance. Islamic Management Review, 5(1), 45-60. Santoso, B. (2022). Collaboration and Innovation in Waqf-Based Business Development. Business and Islamic Economics Journal, 9(2), 156-171. Wahid, H. (2023). Integration of Local Wisdom in the Development of Productive Waqf. Journal of Islamic Social Sciences, 4(1), 34-49. Widodo, H. (2022). Monitoring and Evaluation System of the Sustainable Waqf Program. Journal of Islamic Economics and Development, 5(2), 156-171. Wijaya, H. (2023). Mentoring System in Waqf-Based Entrepreneurial Development. Islamic Economics Review, 8(2), 134-149. Yusuf, M. (2023). Monitoring and Evaluation System of the Productive Waqf Program. Islamic Economics Studies, 5(1), 78-93.